Genome-Wide Analysis of Odorant-Binding Proteins and Chemosensory Proteins in the Bean bug Riptortus pedestris - Li, Jin-Bu; Yin, Mao-Zhu; Yao, Wei-Chen; Ma, Sai; Dewer, Youssef; Liu, Xing-Zhou; Wang, Yue-Ying; Wang, Chao-Wei; Li, Bao-Ping; Zhu, Xiu-Yun (Frontiers in Physiology, 2022)
Insects have sensitive olfactory systems to interact with environment and respond to the change in host plant conditions. Key genes in the system can be potential targets for developing new and efficient pest behaviour control methods. Riptortus pedestris is an important soybean pest in East Asia and has caused serious damage to the soybean plants in Huang-Huai-Hai region of China. However, the current treatment of pests is dominated by chemical insecticides and lacks efficient sustainable prevention and control technologies. In this study, we identified 49 putative odorant-binding proteins (OBPs) (43 were new genes) and 25 chemosensory proteins (CSPs) (17 were new genes) in R. pedestris genome. These OBP and CSP genes are clustered in highly conserved groups from other hemipteran species in phylogenetic trees. Most RpedOBPs displayed antennal-biased expression. Among the 49 RpedOBPs, 33 were significantly highly expressed in the antennae, including three male-biased and nine female-biased. While many RpedCSPs were detected both in the antennae and in non-antennal tissues, only 11 RpedCSPs displayed antennal-biased expression, in which four RpedCSPs were male-biased and five RpedCSPs were female-biased. Some OBP and CSP genes showed sex-biased expression profiles. Our results not only provide a foundation for future exploration of the functions of RpedOBPs and RpedCSPs but also aid in developing environmentally friendly insecticides in the future.